Tongbi Huoluo Decoction alleviates cartilage degeneration in knee osteoarthritis by inhibiting degradation of extracellular matrix - Weijian Chen; Weinian Liu; Tao Jiang; Lingyun Liu; Qi He; Tianye Lin; Jiayuan Zhang; Liwei Huo; Xuemeng Xu; Haibin Wang; Du Liang; Wengang Liu (BMC, 2023)
Abstract Background Knee osteoarthritis (KOA) is an age-related degenerative disease characterized by abrasion of articular cartilage. Tongbi Huoluo Decoction (TBHLD) has been transformed from the famous traditional Chinese medicine Duhuo Jisheng Decoction, which can effectively alleviate pain symptoms in KOA. However, the active components and mechanisms of TBHLD in treating KOA have not yet been elucidated. The purpose of the study was to demonstrate the molecular mechanism of TBHLD in treating KOA. Methods The components and targets of TBHLD and KOA were collected from multiple databases, and the protein to protein interaction (PPI) network was constructed. Next, we performed topological calculation and enrichment analysis. Besides, we performed virtual screening for molecular docking and molecular dynamics simulation (MDS). Furthermore, the vitro and vivo experiments were performed to evaluate the validity and mechanism of TBHLD. Results 206 active components and 187 potential targets were screened from Tongbi Huoluo Decoction. A total of 50 intersecting genes were identified between TBHLD and KOA, 20 core targets were calculated by network topology analysis. The core targets were enriched in the ECM interaction pathways. The results of virtual screening for molecular docking and MDS showed that the active components of TBHLD had steady binding conformations with core genes. Moreover, we identified 32 differential serum components in TBHLD-containing serum using LC-MS, including 22 upregulated and 10 downregulated serum components. TBHLD improved the proliferation activity of OA chondrocytes, decreased the expression of Col1a1, Col1a2, Mmp2, Mmp13 in OA chondrocytes, ameliorated the cartilage lesions and restored the cartilage abrasion. Conclusion TBHLD inhibited degradation of cartilage ECM by regulating the expression of type I collagens and Mmps to ameliorate cartilage degeneration in KOA.